2021
DOI: 10.1097/mpg.0000000000003317
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Nutrition and Gastrointestinal Complications in Pediatric Patients on Extracorporeal Membrane Oxygenation

Abstract: Objectives: To assess the safety of enteral nutrition (EN) in children on extracorporeal membrane oxygenation (ECMO). To describe nutritional status and the characteristics of the nutritional support in this population. Methods: A retrospective single-center analysis (2006–2016) including children <18 years on ECMO. Demographic data, nutritional status, characteristics of nutritional support, and development of gastrointestinal (GI) complications were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…No randomized clinical trials were identified in this literature search. Studies did not always specify where the samples were obtained, but seven studies specified the PICU (2, 8, 13, 18, 19, 21, 22). Five studies were conducted in The Netherlands (12, 17, 19, 20, 24), four studies in the United States (9, 13, 18, 23), two studies in Spain (2, 21), one study in Singapore (8), one study in China (25), and one study in Thailand (22).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…No randomized clinical trials were identified in this literature search. Studies did not always specify where the samples were obtained, but seven studies specified the PICU (2, 8, 13, 18, 19, 21, 22). Five studies were conducted in The Netherlands (12, 17, 19, 20, 24), four studies in the United States (9, 13, 18, 23), two studies in Spain (2, 21), one study in Singapore (8), one study in China (25), and one study in Thailand (22).…”
Section: Methodsmentioning
confidence: 99%
“…In the five studies that listed sex, both males and females were represented evenly (8, 9, 13, 17, 23, 24). Neonatal pulmonary and cardiac diseases were the greatest underlying diagnoses requiring ECMO (2, 8, 9, 12, 17–25). Four studies evaluated patients who only received EN (9, 12, 13, 20).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations